Process and Equipment Improvement for Nickel Brush Plating Application - Marek, Martin; Novak, Martin; Rytina, Tomas; Durakbasa, Numan M. (Manufacturing Technology Journal, 2017)
The purpose of this paper is to provide an overview of process and equipment improvements for nickel brush plating applications. At the beginning of this project the company used methodology from a subsidiary which does nickel brush plating. Over time, it turned out that it would require a total redesign of the process, because it wasn't compliant with Czech legislation. We knew that without improvements the process could not move forward, therefore, we mainly focused on safety, equipment, accuracy and better quality. In this work we have been using many elements from quality management such as 6Sigma methodology, Ishikawa diagrams, 5why methods, 5S, etc.This project included many people from different sectors such as designers, technicans, material engineers, facility and maintenance, production, quality engineers, EHS engineers etc. This team came with a completely new and unique technical solution for the covered equipment which had never been built in the past in this company or by brush plating process.
Keywords: nickel; environment; ergonomic; construction; safety